Cultivating the Underutilized: Non -Timber Forest Produce in Jimma Zone, Ethiopia - Asefa Teferi; Aklilu Amsalu (Journal of Agricultural Extension Management, 2025)
Production of non-timber forest products (NTFPs) by forest fringe communities has invaluable importance, both from the perspective of rural livelihood security and resource conservation. It ensures food availability particularly during slack periods and provides cash income when other income sources such as coffee are non-existent. Despite the rich potential of Jimma zone for NTFPs, the community has not benefited from the multiple functions of the natural afromontane forest in the area. This study was conducted to assess the state of production and utilization of NTFPs in the · study area, and to identify major production challenges and opportunities. The analysis was made using both primary and secondary data. Descriptive statistics were used to examine the association between different groups and the degree of integration with NTFPs. The study found that pest incidence, lack of inputs, shortage of land and limited skilled personnel, absence of irrigation and the expansion of chat were the major production constraints identified. It was also found that the different wealth groups depend on NTFPs to varying degrees. Hence, the study underscores the importance of strengthening extension service, access to credit, control of wild animals, promoting farmers’ field school and creating forward and backward linkages.